2020
DOI: 10.1111/apm.13086
|View full text |Cite
|
Sign up to set email alerts
|

Expression of laminin‐5 gamma 2 chain predicts invasion of extramammary Paget’s disease cell

Abstract: Expression of laminin-5 gamma 2 chain predicts invasion of extramammary Paget's disease cell. APMIS. 2021; 129: 3-8. Extramammary Paget's disease (EMPD) is a rare malignant skin neoplasm characterized by intraepidermal proliferation of tumor cells. The tumor cells of EMPD may sometimes invade into the dermis or metastasize into the regional lymph nodes. Several studies have proposed mechanisms underlying the increased invasiveness of EMPD; however, molecular markers indicating invasiveness have yet to be well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…In uterine cervical adenocarcinoma, a gynecological malignancy similar to that in the present study, the cytoplasmic expression of Lam5γ2 chain was observed as the stage of the disease increased from intraepithelial carcinoma through microinvasive carcinoma to invasive carcinoma [24]. A previous report about Paget's disease showed a similar tendency between non-invasive and invasive cases, similar to the present study [25].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In uterine cervical adenocarcinoma, a gynecological malignancy similar to that in the present study, the cytoplasmic expression of Lam5γ2 chain was observed as the stage of the disease increased from intraepithelial carcinoma through microinvasive carcinoma to invasive carcinoma [24]. A previous report about Paget's disease showed a similar tendency between non-invasive and invasive cases, similar to the present study [25].…”
Section: Discussionsupporting
confidence: 90%
“…Lam5 is composed of three short-chain subunits, α, β, and γ that consists of α3, β3, and γ2 chains, respectively [10][11][12][13][14]. It was recognized as a ligand for urinary-type plasminogen activator receptor, uPAR, in previous studies but has recently also been used as a marker for tumor cell invasion in some human malignancies [21][22][23][24][25]. Among these three subunits, the Lam5γ2 has been reported to show aberrant expression during the development and progression of various malignant tumors [11,12,[15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Laminin, a major component of the extracellular matrix, has been found to have a significant impact on vascular biological function ( Biswas et al, 2017 ; Qin et al, 2017 ). Specifically, laminin-5 is a laminin isoform consisting of α3, β3, and γ2 chains and has been reported to induce neovascularization ( He et al, 2019 ; Qian et al, 2021 ; Tohmatsu et al, 2021 ). In a study conducted by He et al, the molecular mechanism of ATG7 regulating cerebrovascular formation was investigated ( He et al, 2019 ).…”
Section: Atg7 Regulates Angiogenesis Via Non-autophagic Pathwaysmentioning
confidence: 99%